IL-6 Prevents Lung Macrophage Death and Lung Inflammation Injury by Inhibiting GSDME- and GSDMD-Mediated Pyroptosis during Pneumococcal Pneumosepsis - Xuemei Gou; Wenchun Xu; Yusi Liu; Yang Peng; Wenlong Xu; Yibing Yin; Xuemei Zhang (Microbiology Spectrum, 2022)
ABSTRACT Streptococcus pneumoniae is a leading bacterial cause of a wide range of infections, and pneumococcal pneumosepsis causes high mortality in hosts infected with antibiotic-resistant strains and those who cannot resolve ongoing inflammation. The factors which influence the development and outcome of pneumosepsis are currently unclear. IL-6 is critical for maintaining immune homeostasis, and we determined that this cytokine is also essential for resisting pneumosepsis, as it inhibits macrophage pyroptosis and pyroptosis-related inflammation injury in the lung. IL-6 affected infection outcomes in mice and exerted a protective role, primarily via macrophages. We further found that IL-6 deficiency led to increased lung macrophage death and aggravated lung inflammation, and that exogenous administration of IL-6 protein could decrease macrophage death and alleviate lung tissue inflammation. IL-6 also protected Streptococcus pneumoniae-induced lung macrophage death and lung inflammation injury by inhibiting gasdermin E (GSDME)- and gasdermin D (GSDMD)-mediated pyroptosis. Together, these data reveal a novel mechanism for the development of pneumosepsis and the critical protective role of IL-6. These findings may assist in the early identification and treatment of pneumococcal pneumosepsis. IMPORTANCE Pneumococcal pneumonia has been a significant cause of morbidity and mortality throughout human history. Failing to control pneumococcal pneumonia and resolve ongoing inflammation in a host can cause sepsis, namely pneumococcal pneumosepsis, and death ensues. Few theories have suggested an optimally therapeutic option for this infectious disease. The interleukin-6 (IL-6, a cytokine featuring pleiotropic activity) theory, proposed here, implies that IL-6 acts as a protector against pneumococcal pneumosepsis. IL-6 prevents lung macrophage death and lung inflammation injury by inhibiting a caspase-3-GSDME-mediated switch from apoptosis to pyroptosis and inhibiting caspase-1-GSDMD-mediated classic pyroptosis during pneumococcal pneumosepsis. Thus, IL-6 is an important determinant for controlling bacterial invasion and a homeostatic coordinator of pneumococcal pneumosepsis. This study clarifies a novel mechanism of occurrence and development of pneumonia and secondary sepsis following a Streptococcus pneumoniae infection. It is important for the early identification and treatment of pneumococcal pneumosepsis.